FUNGSI PERSEPSI HARGA PRODUK PERBANKAN, CITRA MEREK, DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN SESEORANG MENJADI NASABAH BANK MUAMALAT MADIUN - Velin Anesti; Hartirini Warnaningttyas; Ahadiati Rohmatiah (ITB AAS Indonesia Surakarta, 2026)
This study aims to examine the role of perceptions of banking product prices, brand image, and service quality in influencing a person's decision to become a customer of Bank Muamalat Madiun. The research method used was quantitative, with primary data obtained. The analysis results show that perceptions of banking product prices, brand image, and service quality simultaneously have a significant influence on the decision to become a customer. Partially, brand image and service quality have a positive and significant influence, with service quality being the most dominant variable influencing customer decisions. Price perception also has a positive influence, but its contribution is relatively smaller compared to the other variables.